Q10 measures of metabolic performance and critical swimming speed in King George whiting Sillaginodes punctatus. Issue 5 (16th February 2017) - Mazloumi, N.; Johansen, J. L.; Doubleday, Z. A.; Gillanders, B. M.
Abstract : This study examined thermally driven changes in swimming performance and aerobic metabolism ( Q 10 and aerobic scope of activity) of adult King George whiting Sillaginodes punctatus to the coldest (16° C) and the warmest (26° C) temperature encountered by this species. Compensation of aerobic scope, higher maximal swimming speeds and a maintained capacity to repay oxygen debt indicate that this species is capable of thermal acclimation to conditions expected under global warming.